Endometrial nitric oxide synthase activity in mares susceptible or resistant to persistent breeding‐induced endometritis and the effect of a specific iNOS inhibitor in vitro. (14th March 2018) - Khan, FA; Chenier, TS; Foster, RA; Hewson, J; Scholtz, EL
Contents: Emerging research suggests that the nitric oxide system may play a role in persistent breeding‐induced endometritis (PBIE) in the mare. Differences in uterine nitric oxide (NO) levels between mares susceptible or resistant to PBIE and a dose‐dependent inhibitory effect of NO on uterine contractility have been demonstrated. The objectives of this study were to investigate the difference in total nitric oxide synthase (NOS) activity of the endometrium between susceptible and resistant mares and the effect of a specific inducible nitric oxide synthase (iNOS) inhibitor on the endometrial NOS activity in vitro. Six susceptible and six resistant mares were selected based on preset criteria and the results of an intrauterine challenge with killed spermatozoa during oestrus. Endometrial biopsy samples were collected 24 hr post‐challenge and cultured at 37°C for 24 hr in L‐arginine supplemented minimum essential medium with or without a specific iNOS inhibitor (1, 400 W dihydrochloride, 1 mM). The medium and the cultured endometrial tissue were collected after 24 hr of culture and assayed for NO and total protein, respectively. Total NO content of the medium, normalized to endometrial tissue wet weight or total protein, was used as a measure of endometrial NOS activity. Non‐parametric tests were applied for statistical analysis. Susceptible mares had significantly greater endometrial NOS activity than resistant mares. The iNOS inhibitor treatment significantly reduced NOS activity in endometrial samples derived from susceptible and resistant mares. These findings provide a basis for in vivo testing of specific iNOS inhibitors as preventative or therapeutic options for PBIE in mares.